Change of Scale Formulas for Wiener Integrals Related to Fourier-Feynman Transform and Convolution. (26th June 2014) - Kim, Bong Jin; Kim, Byoung Soo; Yoo, Il
Abstract : Cameron and Storvick discovered change of scale formulas for Wiener integrals of functionals in Banach algebraS on classical Wiener space. Yoo and Skoug extended these results for functionals in the Fresnel classF ( B ) and in a generalized Fresnel classF A 1, A 2 on abstract Wiener space. We express Fourier-Feynman transform and convolution product of functionals inS as limits of Wiener integrals. Moreover we obtain change of scale formulas for Wiener integrals related to Fourier-Feynman transform and convolution product of these functionals.